Peculiaridades sintácticas del “SE” en el lenguaje infantil - Esquivel Villafana, Jorge (2000)
Facing the study of the syntactic aspects related to the pronominal form "se" in a particular language will always constitute a challenge to be taken into account if one intends, at the same time, to be rigorous and exhaustive. In principle, because there is still no agreement among specialists even about all the significant values or nuances of "se". An attempt has been made to describe it by taking as the axis or central point of treatment the syntactic feature of reflexivity in order to consider the different forms as modalities of reflexives; probably on the understanding that of all the forms of "se" the reflexive is the most widespread, when in reality, the true reflexives constitute only part of what usually appears as production with "se".